Circular Gastronomy in Hospitality Operations: An Embedded Qualitative Case Study from Bali - I Wayan Sonder; Randhi Nanang Darmawan; Ni Wayan Sumariadhi; Ni Wayan Anggreni; Saroh Fitriani (Jurnal Ekonomi dan Bisnis Jagaditha)
Circular gastronomy, the integration of circular economy principles into culinary operations, provides a strategic response to sustainability challenges in hospitality, particularly in Bali where mass tourism intensifies environmental pressures. This study explores its implementation at Natya Hotels & Resorts Bali through observations and in-depth interviews with executive chefs. Using an embedded qualitative case study design, data were collected through observations and semi-structured interviews with three executive chefs across three Natya Hotels & Resorts properties in Bali. Findings reveal a triadic model comprising material cascade utilization, kitchen efficiency (portion control, FIFO, energy-saving practices), and community-based symbiosis in waste redistribution and composting. The resorts achieved F&B waste below 5%, significantly lower than the industry average of 20–30%, while generating 10–15% cost savings, empowering local SMEs, and preserving culture through Balinese cooking classes. The alignment of corporate policies with local government regulations further creates an enabling environment for circular practices. Despite challenges in transparency and scalability, the study demonstrates how embedded circularity integrates economic, ecological, and socio-cultural benefits, offering a replicable blueprint for sustainable hospitality and contributing to SDG 12.3 and SDG 8.9.